Women community college presidents in the Midwest: experiences in leading their campuses - Krull, Kimberly W., author; Anderson, Sharon K., advisor; Littrell, John, committee member; Davies, Tim, committee member; Hall, Bruce, committee member (Colorado State University. Libraries, 2011)
This phenomenological study has examined the lived experiences of 14 women community college presidents in the Midwest. As community colleges face extraordinary challenges, leaders will be required to be innovative, creative, and responsive to the changing environments. With the impending turnover of community college presidencies by 2016 and the potential for women to assume those leadership positions, an understanding of their day-to-day experiences will prove valuable to prepare the next generation of women leaders. From the in-depth analysis of face-to-face interviews with study participants, four themes have emerged: Influences to the Presidency, Determination and Perseverance, Sense of Progress and Success, and Advice for Future Women Leaders. Broader interpretation of these themes has identified the unintentional nature of the participants' pathways to their presidencies, the impact that mentors or colleagues had on their professional development and decisions, and the self-actualization that occurred to help them realize they could be a successful president. As the presidents discussed the challenges they faced, which included leadership vacuums, gender issues, facility and financial issues, and the balance between personal and professional responsibilities, their determination and sheer will to move forward and be successful was apparent. They identified progress and success in both tangible and intangible ways. Much of the progress was dependent on their leadership skills and styles. As these presidents offered advice for future women leaders, modeling integrity, honesty, and ethics were at the forefront of all the discussions. They believed strongly that women leaders must be self-confident and utilize innate skills and strengths to create change. Their working relationship with the board and internal campus community were key factors in institutional stability and positive progress. The presidents viewed themselves as change agents for higher education. Relating the various themes to the research questions and current literature identified opportunities for further discussion. Within the four overarching themes, participants discussed the need for women leaders to have doctoral degrees, professional-development opportunities, mentors, job-shadowing, and broad-based exposure to all types of learning opportunities in order to develop needed leadership skills. Further studies are encouraged to discern how to best acquire and develop necessary leadership skills, the presidents' perceptions of preparedness for leadership, the impact of mentoring of professional development, and the correlation between leadership success and the doctoral degree area of study. Additionally, researchers could study the strengths and weaknesses of internal versus external leadership-development programs, the retention of aspiring women leaders based on leadership development programs, and the impact on institutions of the presence or absence of succession planning. Gender issues should continue to be studied as well to discern how barriers to women might be diminished.
Keywords: women; community college leadership; leadership; leadership development; phenomenology; transformational leadership